INTERPERSONAL RELATIONS AND MEDIATION STYLES: A SOCIO-PSYCHOLOGICAL ANALYSIS - Dimitrova, Stefka (E-Journal VFU, 2025)
The article presents a socio-psychological analysis of mediation, with a special focus on the interpersonal relations between mediators and their clients. Different mediation styles – official, psychotherapeutic, controlling, empathetic, and business – are examined in relation to the mediators’ personality characteristics. The results reveal significant differences in the mutual perceptions of both groups and highlight the importance of trust and cooperation for the effective resolution of conflicts. Mediation emerges not only as a tool for negotiation but also as a complex socio-psychological process.
Keywords: mediation; social orientations; professional activity of the mediator; interpersonal relations; negotiation styles; psychological characteristics